I think the answers True hope this helps
Yes because you multiply first so in this case you multiply 7 and 3 first. Since the second expression is in parenthesis you do that first just like you do 7 times 3. Then you just add 2 to that. The value of both expressions is 23
Answer:
Slope of Function B = – Slope of Function A
Step-by-step explanation:
Slope of function A=![-2](https://tex.z-dn.net/?f=-2)
Slope of function B=$\frac{3-1}{3-2}=2$
Your answer would be f(0)=7.07
1. Substitute 0 into x.
2(0)^2+5√(0+2)
2. Simplify
2(0)+5√2
0+5√2
5√2
7.07
This is the simplest and rounded form, therefore, it is the answer to your question.